Attitudes Toward Different Types of Chinese-English Code-Switching - Hong Liu (SAGE Open, 2019)
This study investigates language attitudes held by Chinese-English bilinguals toward two types of switching to English in mandarin Chinese discourse, that is, intraclausal and interclausal switching. Participants with varying degrees of English proficiency were sampled from four cities in mainland China and one oversea city, London. A variation of matched-guise technique, open guise technique, was used to collect attitudinal responses toward code-switching. Quantitative analyses showed that the participants generally downgraded code-switching on social likability, with interclausal switching receiving the lowest ratings. In terms of social-economic status, however, interclausal switching was rated the highest and the intraclausal type the lowest. Such evaluative responses were consistent across genders and the cities of interest. The theoretical and methodological implications of the study are discussed.